2016
DOI: 10.1371/journal.pone.0161896
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine and Phosphatidylethanolamine Bind to Protein Z Cooperatively and with Equal Affinity

Abstract: Protein Z (PZ) is an anticoagulant that binds with high affinity to Protein Z-dependent protease inhibitor (ZPI) and accelerates the rate of ZPI-mediated inhibition of factor Xa (fXa) by more than 1000-fold in the presence of Ca2+ and phospholipids. PZ promotion of the ZPI-fXa interaction results from the anchoring of the Gla domain of PZ onto phospholipid surfaces and positioning the bound ZPI in close proximity to the Gla-anchored fXa, forming a ternary complex of PZ/ZPI/fXa. Although interaction of PZ with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Because of its significance in cellular processes, the identification of interactions between proteins and PS is essential for understanding its regulatory roles [21]. Several PS-binding proteins have been reported [22]; however, only a few studies have reported the interaction between viral proteins and lipids despite its essential function on viral entry and budding [23]. In this study, we showed that HCV p7 prefers PS over other negatively charged phospholipids (PA, PG, PI, and CL).…”
Section: Discussionmentioning
confidence: 60%
“…Because of its significance in cellular processes, the identification of interactions between proteins and PS is essential for understanding its regulatory roles [21]. Several PS-binding proteins have been reported [22]; however, only a few studies have reported the interaction between viral proteins and lipids despite its essential function on viral entry and budding [23]. In this study, we showed that HCV p7 prefers PS over other negatively charged phospholipids (PA, PG, PI, and CL).…”
Section: Discussionmentioning
confidence: 60%
“…Since the Hill coefficients are above 1, the binding of the three TIM proteins are cooperative and thus sensitive to PS surface density [53]. Unlike the cooperativity measured for Annexin V, the PKC family, or Protein Z, the cooperativity of the TIM proteins cannot be explained by multiple PS or Ca binding sites [25,26,28]. Alternative mechanisms can underly cooperative binding such as the protein’s non-specific electrostatic interactions with neighboring PS.…”
Section: Tim Proteinsmentioning
confidence: 99%
“…Annexin V, a PS-receptor suspected to inhibit blood coagulation by outcompeting coagulation factors with C2 and Gla PS-binding domains, binds cooperatively to PS and calcium, indicating a preference for membranes with high PS surface density [25,26]. Similarly, Protein Kinase C (PKC) family members also bind PS cooperatively [27] and the coagulation factor Protein Z binds both PS and phosphatidylethanolamine (PE), another lipid normally enriched on the inner leaflet that flips out during apoptosis [28]. Considering that PS receptors are each specialized for particular functions, such as the recognition of apoptosis, signal transduction, exocytosis, phosphorylation of phosphoinositide, and coagulation [10], it is likely that PS-binding proteins recognize both PS and the membrane context of PS presentation.…”
Section: Introductionmentioning
confidence: 99%
“…C6PS also appears to promote dimer formation of factor Xa and such dimerization may prevent factor Xa binding to factor Va due competition . Furthermore, this short chain lipid binds to factor IXa and protein Z, possibly affecting functions of these molecules. Short chain phospholipids might be produced by oxidation, but this has not been reported to our knowledge; so the pathophysiologic relevance of short chain PLs like C6PS remains unknown.…”
Section: Plasma Phospholipid Derivatives Blood Coagulation and Vtementioning
confidence: 99%